Reforming the legal framework for construction dispute resolution in Nigeria: a preliminary literature survey - Raji, Barakat; Ali Mohamed, Ashgar Ali; Oseni, Umar Aimhanosi (Zesdyzar Rokman Resources, 2015)
This paper presents a preliminary literature review on the prospects of reforms of the legal framework for construction dispute resolution in Nigeria. At the moment, the prevailing method of resolving construction disputes in Nigeria are litigation and arbitration which have caused series of delays in major construction works. This paper seeks to propose effective legal framework for dispute resolution processes for the construction industry in Nigeria. While relying on some recent advances recorded in Malaysia and Singapore. While the method adopted is purely doctrinal legal research, the study identifies the relevance of alternative dispute resolution (ADR) processes in the construction industry in Nigeria as utilised elsewhere. The study found that the building blocks for the proposed dispute resolution framework in the construction industry in Nigeria are already in place but they need to be properly placed for a sustainable framework. The use of qualitative approach was to enable the study to know the experiences, perspectives and challenges facing the stakeholders in the construction industry in the use of the existing processes for construction dispute resolution. This approach will validate the need for effective construction dispute resolution processes. This is proposed to be part of the overall project management plan in any construction project so that the final project performance is not negatively impacted.